Analysis of the behavior of informal tourism in the city of Cartagena de Indias, Colombia - Morelos-Gómez, José; Cardona-Arbeláez, Diego; Lora-Guzmán, Harold (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this document, the behavior of the supply, demand and preferences of tourism of young backpackers, who visit the city of Cartagena de Indias, Colombia, are analyzed. The research is quantitative, descriptive and transversal in scope, where 196 visitors who used low-cost informal tourist services were surveyed during 2018. It was found that the majority of informal tourists are young people between 18 and 30 years old (68% ), professionals, who are looking for a different, low-cost experience, preferably to travel with a group of friends, spend little money and stay in cheap places. In 95% of the cases, they choose sites that offer breakfast service and internet connection, considered a priority, and prefer to stay in places located mainly in the historic center of the city, due to their bohemian and multicultural atmosphere. It stands out that 67% of those surveyed have a university level of training. It concludes with the need for tour operators to complement the services they offer, so that they meet the expectations of backpackers visiting Cartagena de Indias.